1997
DOI: 10.3109/08923979709007656
|View full text |Cite
|
Sign up to set email alerts
|

The Prostaglandin Analogs, Misoprostol and SC-46275, Potently Inhibit Cytokine Release from Activated Human Monocytes

Abstract: Inflammatory mediator release is one of the body's responses to tissue injury and inflammation. These mediators, such as interleukin-1 beta (I1-1 beta), tumor necrosis factor (TNF-alpha), and products of arachidonic acid metabolism, are themselves proinflammatory. Purified human monocytes stimulated in vitro with E. coli-derived lipopolysaccharide (LPS) will release these key cytokines along with various other eicosanoid mediators. Monocytes incubated with LPS and the prostaglandin E-1 analog, misoprostol, rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…In addition to direct neuronal damage, PMNs contribute to secondary injury by causing microvessel occlusion and releasing oxygen radicals, cytolytic proteases, and proinflammatory cytokines, which may injure the endothelium [16,17]. Chopp et al reported that a reduction in the number of PMNs reduced post-ischemic tissue damage in the heart, intestine, lung, and liver [18].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to direct neuronal damage, PMNs contribute to secondary injury by causing microvessel occlusion and releasing oxygen radicals, cytolytic proteases, and proinflammatory cytokines, which may injure the endothelium [16,17]. Chopp et al reported that a reduction in the number of PMNs reduced post-ischemic tissue damage in the heart, intestine, lung, and liver [18].…”
Section: Resultsmentioning
confidence: 99%
“…It also inhibits the release of inflammatory cytokines (222). In a small, placebo-controlled, semi-crossover study, tinnitus was improved (reduced severity, improved sleep and concentration) in 33% of subjects during misoprostol treatment (escalating to 800 μg/day), whereas no subjects improved in the placebo group (223).…”
Section: Drug Therapy For Tinnitus: Pharmacological Studiesmentioning
confidence: 99%
“…32) Signaling experiments revealed that MB28767 inhibited forskolin-induced cAMP concentrations in Chinese hamster ovary cells. 33) iv) EP4 agonists: ONO-AE1-329 and cicaprost 16,17) are well known selective EP4 agonists (Figures 1 F and G).…”
Section: Synthesized Ep Agonists I) Ep1 Agonistsmentioning
confidence: 99%